General principles as a source of international law : Art 38(1)(c) of the Statute of the International Court of Justice - Saunders, Imogen (Oxford, UK ; New York, NY : Hart Publishing, an imprint of Bloomsbury Publishing, 2020)
"This book provides a comprehensive analysis of an often neglected, misunderstood and maligned source of international law. Article 38(1)(c) of the Statute of the International Court of Justice sets out that the Court will apply the 'general principles of law recognized by civilized nations'. This source is variously lauded and criticised: held up as a panacea to all international law woes or denied even normative validity. The contrasting views and treatments of General Principles stem from a lack of a model of the source itself. This book provides that model, offering a new and rigorous understanding of Article 38(1)(c) that will be of immense value to scholars and practitioners of international law alike. At the heart of the book is a new tetrahedral framework of analysis - looking to function, type, methodology and jurisprudential legitimacy. Adopting an historical approach, the book traces the development of the source from 1875 to 2019, encompassing jurisprudence of the Permanent Court of International Justice and the International Court of Justice as well as cases from international criminal tribunals, the International Criminal Court and the World Trade Organisation. The book argues for precision in identifying cases that actually apply General Principles, and builds upon these 'proper use' cases to advance a comprehensive model of General Principles, advocating for a global approach to the methodology of the source"--
A framework for analysing general principles -- History of Article 38(1)(c) -- Consideration of Article 38(1)(c) by the PCIJ -- Development of Article 38(1)(c) : 1945-91 -- Development of Article 38(1)(c) by the ICJ : 1992-2019 -- General principles in other courts and tribunals -- Commentary in context -- Global general principles -- A model of general principles.
Includes bibliographical references and index.
Keywords: International Court of Justice -- History; Permanent Court of Arbitration -- History; International Court of Justice; Permanent Court of Arbitration; International law -- History; International law; History